Dead Mountain : the untold true story of the Dyatlov Pass incident - Eichar, Donnie (San Francisco : Chronicle Books, 2013)
Het verhaal van Russische lifters die spoorloos verdwenen en nooit werden terug gevonden. Het boek vertoont vooraan sporen van schade: stukken werden uit de pagina's geknipt.
Includes index.
Keywords: HISTORY / Europe / Russia & the Former Soviet Union; Hiking -- Russia (Federation) -- Ural Mountains Region; Mountaineering accidents -- 20th century -- Russia (Federation) -- Ural Mountains Region; Ural Mountains Region (Russia) -- History -- 20th century